2021
DOI: 10.1002/advs.202103564
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Multi‐Shank Fluorescence Neural Probe for Cell‐Type‐Specific Electrophysiology in Multiple Regions across a Neural Circuit

Abstract: Cell‐type‐specific, activity‐dependent electrophysiology can allow in‐depth analysis of functional connectivity inside complex neural circuits composed of various cell types. To date, optics‐based fluorescence recording devices enable monitoring cell‐type‐specific activities. However, the monitoring is typically limited to a single brain region, and the temporal resolution is significantly low. Herein, a multimodal multi‐shank fluorescence neural probe that allows cell‐type‐specific electrophysiology from mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Flue 4AM has been used as a membrane-permeable, Ca +2 dependent dye, which increases fluorescence on binding of free Ca +2 [86] . Previous studies reported that ES can induce a change in Ca +2 ion concentration of neuron cells, resulting in the increased fluorescence intensity of Flue 4 AM dye in the neuron [87,88]. As As expected, undifferentiated hMSCs (non-neuronal cells) mostly exhibited nonexcitable behavior and failed to exhibit membrane depolarization after ES treatment.…”
Section: Calcium Imaging Of Differentiated Hmscssupporting
confidence: 78%
See 1 more Smart Citation
“…Flue 4AM has been used as a membrane-permeable, Ca +2 dependent dye, which increases fluorescence on binding of free Ca +2 [86] . Previous studies reported that ES can induce a change in Ca +2 ion concentration of neuron cells, resulting in the increased fluorescence intensity of Flue 4 AM dye in the neuron [87,88]. As As expected, undifferentiated hMSCs (non-neuronal cells) mostly exhibited nonexcitable behavior and failed to exhibit membrane depolarization after ES treatment.…”
Section: Calcium Imaging Of Differentiated Hmscssupporting
confidence: 78%
“…Flue 4AM has been used as a membrane-permeable, Ca +2 dependent dye, which increases fluorescence on binding of free Ca +2 [86]. Previous studies reported that ES can induce a change in Ca +2 ion concentration of neuron cells, resulting in the increased fluorescence intensity of Flue 4 AM dye in the neuron [87, 88]. As Figure 7C-D show, after ES, the Fluo-4 fluorescence level of the differentiated hMSCs on both the soft and stiff CS-g-PANI significantly increased compared to cells without electrical stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…1b). Also, the microelectrodes were electroplated with Pt black to enhance the neural recording performance [17][18][19][20][21] . The longterm stability of the probe, including Pt black microelectrodes, was demonstrated in our previously reported study 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, the microelectrodes were electroplated with Pt black to enhance the neural recording performance [17][18][19][20][21] . The longterm stability of the probe, including Pt black microelectrodes, was demonstrated in our previously reported study 21 . In addition, the microfluidic channels were designed to have low fluidic resistance, which enables the delivery of the drug by low pressure that is generated from a miniaturized, electrolytic pump.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, invasive neural interfaces are promising tools because of their ability to collect more sophisticated and direct electrophysiological data [5]. Silicon-based invasive neural interfaces have been widely used, and their performance has been proven in many studies [7][8][9][10]. However, longlasting integration of invasive neural interfaces with the neural tissue is the most challenging issue to be addressed at present [11].…”
Section: Introductionmentioning
confidence: 99%